Greening growth in Asia and the Pacific (Mandaluyong City, 2011)
The report discusses the emerging environmental challenges in the region, and previews ADB's strategies to strengthen its operational emphasis on the environment including climate change, that would help realize green growth for the region.
Keywords: Environmental aspects,Khía cạnh môi trường